2023
DOI: 10.3390/plants12030647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sugarcane (Saccharum spp.) Hybrid F1 Population Phenotypic Diversity and Construction of a Rapid Sucrose Yield Estimation Model for Breeding

Abstract: Sugarcane is the major sugar-producing crop worldwide, and hybrid F1 populations are the primary populations used in breeding. Challenged by the sugarcane genome’s complexity and the sucrose yield’s quantitative nature, phenotypic selection is still the most commonly used approach for high-sucrose yield sugarcane breeding. In this study, a hybrid F1 population containing 135 hybrids was constructed and evaluated for 11 traits (sucrose yield (SY) and its related traits) in a randomized complete-block design dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…For the majority of the traits, except plant height and the number of shoots per clump, the one-way analysis of variance revealed highly significant differences among the 10 seedlings of each cross that were evaluated (Table 1). The results are found to be similar with the findings of Dena et al (2018), Farnsworth and Arioli (2018), Farrag et al (2018) and Xu et al (2023). Since the differences between crosses account for a large portion of the variation within crosses, these seedlings have the potential to produce high cane and sugar yields over the subsequent stage of selection.…”
Section: Analysis Of Variancesupporting
confidence: 88%
See 1 more Smart Citation
“…For the majority of the traits, except plant height and the number of shoots per clump, the one-way analysis of variance revealed highly significant differences among the 10 seedlings of each cross that were evaluated (Table 1). The results are found to be similar with the findings of Dena et al (2018), Farnsworth and Arioli (2018), Farrag et al (2018) and Xu et al (2023). Since the differences between crosses account for a large portion of the variation within crosses, these seedlings have the potential to produce high cane and sugar yields over the subsequent stage of selection.…”
Section: Analysis Of Variancesupporting
confidence: 88%
“…This signified that the most of the seedlings from these crosses performed superior to the population mean. The results obtained are on par with the research done by Bharathi et al (2017), Somu and Nagaraja (2018), Xu et al (2023).…”
Section: Variability Studiessupporting
confidence: 88%
“…The impact of the climate or the environment on crops ultimately manifests in their phenotype, and different climates or environments may affect different traits [42,[44][45][46][47]. In this study, the CV of the twenty traits varied in CK, drought and pluvial conditions.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, the CV of the twenty traits varied in CK, drought and pluvial conditions. Usually, when the CV is greater than 10%, the trait shows significant variation within the population [45,48]. Using the best linear unbiased prediction (control), nine of the twenty traits showed significant variation with a coefficient of variation greater than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity index can more accurately reflect the genetic diversity of resources, with a higher index indicating greater diversity among traits [29]. An analysis of the agronomic trait data of 192 maize germplasms over two years revealed that, aside from plant height and stem-leaf angle, which exhibited significant mean value differences between the years, the mean values of other traits did not differ significantly(Table 1).…”
Section: Diversity Analysis Of Phenotypic Traits In Maize Accessionsmentioning
confidence: 99%